Consequences of Collaborative Governance in CSR: An Empirical Illustration of Strategic Responses to Institutional Pluralism and Some Theoretical Implications. (8th September 2016) - Moratis, Lars
Abstract: Collaborative governance (CG) is becoming the common currency of decision‐making, able to surmount existing institutional constraints to effectively address challenges related to sustainability and social and environmental corporate behavior. CG approaches may however result in institutional complexity. As an illustration of CG in the domain of corporate social responsibility (CSR), the ISO 26000 standard is a legitimate point of reference for organizations worldwide. The standard represents a pluralistic institutional logic that resonates several tensions arising from the domain it tries to standardize, the nature of its development process, its interpretation of CSR and the type of standard it represents. This article aims to identify and examine strategic responses to ISO 26000 by various standards‐related organizations (including national standardization institutes, certification organizations, and service providers) and to contribute to the understanding of strategic responses of organizations to pluralistic institutional logics that result from CG.